Mobile mercury resistance transposons: surveillance and resistance gene cassette variation in wastewater - Pritchard, Alexander C W (2022)
In a wastewater environment, mercury resistance and other antimicrobial metal resistance genes have been observed despite their lack of use clinically. The hypotheses explored whether the change in populations to a rural wastewater treatment plant affects the abundance of Tn21 and similarly identify potential co–occurrence antimicrobial resistance genes carried within or alongside Tn21 and Tn21-like transposable elements. Finally, Tn21 is known to be carried by a wide range of Gram-negative bacteria, however without being able to cross-link Tn21 to the host it is not possible to identify in large scale samples which organisms may in fact carry the mobile element within an environmental sample. Results showed that large-scale population changes impacted the abundance of Tn21 and the carriage of co-occurrent resistance genes. Wastewater treatment processing was also shown to reduce diversity of Tn21 gene cassette arrays of the class I integron and therefore not remove the presence of antimicrobial resistance genes disseminating into the environment. The studies highlight the need for intervention within the wastewater treatment process.